2020
DOI: 10.26434/chemrxiv.12003321.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Semiconductive Microporous Hydrogen-Bonded Organophosphonic Acid Frameworks

Abstract: <p>We report the first semiconductive, proton-conductive, microporous hydrogen-bonded organic framework (HOF) derived from phenylphosphonic acid and 5,10,15,20‐tetrakis[<i>p</i>‐phenylphosphonic acid] porphyrin (known as GTUB5). The structure of GTUB5 was characterized using single crystal X-ray diffraction (XRD). A narrow band gap of 1.56 eV was extracted from a UV-Vis spectrum of pure GTUB5 crystals, in excellent agreement with the 1.65 eV band gap obtained from density functional theory ca… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…1), were pretreated with various bivalent metal ions at a pH close to the cellular milieu (pH 7.4) before recording absorption and fluorescence spectra. The visible absorption of both sensors in the buffer-control treatment showed maxima in the range of 380-430 nm, with a typical Soret peak at around 416 nm, already observed in our recent studies [36,44] and also by others [45] . Ca 2+ or Mg 2+ treatment did not shift the position of the Soret maximum, but slightly raised the intensity of the absorption spectrum causing a higher fluorescence, characteristic for non-ratiometric metal-ON fluorescence sensors.…”
Section: Resultssupporting
confidence: 81%
“…1), were pretreated with various bivalent metal ions at a pH close to the cellular milieu (pH 7.4) before recording absorption and fluorescence spectra. The visible absorption of both sensors in the buffer-control treatment showed maxima in the range of 380-430 nm, with a typical Soret peak at around 416 nm, already observed in our recent studies [36,44] and also by others [45] . Ca 2+ or Mg 2+ treatment did not shift the position of the Soret maximum, but slightly raised the intensity of the absorption spectrum causing a higher fluorescence, characteristic for non-ratiometric metal-ON fluorescence sensors.…”
Section: Resultssupporting
confidence: 81%
“…[39][40][41] We also reported the first semiconductive permanently microporous hydrogen-bonded phosphonic acid framework (constructed using the p-H 8 TPPA linker) with a bandgap of 1.54 eV. [42] As summarized in a recent review article, [14] the number of threedimensional electrically conductive MOFs in the literature is limited. Thus, one of the important goals in MOF chemistry is to synthesize three-dimensional electrically conductive MOFs.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] In a related study, we reported the first semiconductive permanently microporous hydrogen-bonded phosphonic acid framework (constructed using the p-H 8 TPPA linker) with a band gap of 1.54 eV. 36 To the best of our knowledge, no semiconductive zincphosphonate MOFs have been reported in the literature. Thus, in this work, we used the polyaromatic porphyrin core with zinc IBUs to synthesize a semiconductive zinc-phosphonate MOF known as GTUB3.…”
Section: Semiconductive Phosphonate Mofsmentioning
confidence: 99%